2016
DOI: 10.11114/ijsss.v4i11.1941
|View full text |Cite
|
Sign up to set email alerts
|

The Arrested Development of Golden Rice: The Scientific and Social Challenges of A Transgenic Biofortified Crop

Abstract: Since its initiation to reduce the global public health crisis of vitamin A deficiency (VAD), the Golden Rice (GR) Project has met with both successes and challenges. After 16 years of its scientific breakthrough in 2000 with the GR prototype to produce β-carotene in rice grain, it has yet to be released. As the first biofortified crop developed with transgenic technologies designed to reduce the micronutrient deficiency, GR has met controversy and even academic scandal. This review updates the science and sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Consumption of orange cassava showed a small but significant increase in retinol and β‐carotene concentrations in plasma of Kenyan children compared to controls eating white cassava (Talsma et al ., ). Attempts at undertaking similar trials for Golden Rice have met with voracious criticism, which even led to retraction of the paper on which the claims of bioefficacy were based (Tang et al ., ; Lee & Krimsky, ).…”
Section: How Successful Has Metabolic Engineering Been In Biofortificmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumption of orange cassava showed a small but significant increase in retinol and β‐carotene concentrations in plasma of Kenyan children compared to controls eating white cassava (Talsma et al ., ). Attempts at undertaking similar trials for Golden Rice have met with voracious criticism, which even led to retraction of the paper on which the claims of bioefficacy were based (Tang et al ., ; Lee & Krimsky, ).…”
Section: How Successful Has Metabolic Engineering Been In Biofortificmentioning
confidence: 99%
“…Rice biofortification in provitamin A is, of course, the prime example of this. However, the alternative of conventional breeding of biofortified rice has had little success for iron and folate, and no success with enrichment of provitamin A, although zinc‐enriched varieties of rice have been released (Lee & Krimsky, ).…”
Section: Biofortification To Address Deficiency Diseasesmentioning
confidence: 99%
“…Another research group in Japan found that compared to single introduction of individual genes, introduction of multiple iron homeostasis genes is more effective for iron biofortification (Masuda et al, ). However, widespread skepticism about transgenic food limits the promotion of transgenic high‐iron rice worldwide (Davidsson, ; Lee & Krimsky, ; Taheri, Azadi, & D’Haese, ).…”
Section: Ways To Improve Low Iron Levelsmentioning
confidence: 99%
“…For instance, Golden Rice, a transgenic rice variety with enhanced pro-vitamin A to help alleviate vitamin A deficiency in developing countries, has both benefitted and suffered from media coverage. Also, the media has partly influenced the rice's current regulatory status, a regulatory limbo [44]. For as sensitive an issue as agricultural biotechnology, the media can sway the direction of public perception with unsubstantiated advocate, neutral and fair coverage or sensationalized disapproval.…”
Section: Building Public Awareness About Agricultural Biotechnologymentioning
confidence: 99%